Science, technology, and politics : policy analysis in Congress - Bryner, Gary C (Boulder : Westview Press, 1992)
In-depth case studies of environmental, biomedical, biotechnological, communications and economic-policy issues show how technology is assessed in the US Congress, the role technology plays in the formulation of public policies, and what the prospects are for improving technical policy-making.
Includes bibliographical references and index.
Keywords: Science and state -- United States; Technology and state -- United States